Evaluasi Keterlambatan Pengiriman Barang dengan Menggunakan Metode Six Sigma - Somadi Somadi (Jurnal Logistik Indonesia, 2020)
One of the things that is usually the basis of consumers choosing a company is the quality of service. So the quality of service becomes important because it will have a direct impact on companies such as PT. Z. One type of service provided is in the form of on time delivery. But in practice the delivery time is not always achieved, sometimes there is still a delay. This study aims to identify the types of shipping delays that often occur and the factors causing delays in shipping and to design improvement strategies to minimize the occurrence of shipping delays at PT. Z. The method used in this study is to use the Six Sigma method with the DMAIC approach. Based on the results of the study that the type of delay that often occurs and needs to be addressed is the delay in sending documents. The factors that cause delays in shipping are caused by delays in the stuffing plan, errors in informing shipping instructions to EMKL, ship booking delays, miss communication, shortage of trucking fleets and unorganized work spaces. The strategies to minimize the occurrence of delays in the delivery of goods namely adding labor, working in a focused and meticulous manner, establishing active interaction between divisions, communicating various shipping information to the EMKL, finding new trucking fleet vendors, and creating a comfortable and neat working atmosphere.